Influence of testing configuration on the behaviour of energy-absorbing, self-drilling rockbolts under impact loading - Knox, G; Hadjigeorgiou, J (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
A major challenge in block caving operations is the selection of ground support that can accommodate the deformation associated with the significant stress changes during the life of an operation. This is best accomplished using high energy-absorbing rockbolts. An additional operational constraint is the installation of the selected rockbolts in heavily fractured or poor ground conditions. Under these constraints, the use of energy-absorbing, self-drilling rockbolts becomes an attractive option. The ISRM suggested method for determining the performance of energy-absorbing rockbolts in the laboratory relies on dropping a given mass from a specific height employing 2 testing configurations to transfer the kinetic energy of the falling mass to the rockbolt that is installed in a steel tube. The continuous tube configuration simulates an impact load directly applied onto the rockbolt plate while the split tube represents a loading condition on a rockbolt when a rock block is ejected by an impact thrust. The in situ loading of a rockbolt under seismic loads is more complex. This paper investigates the influence of the split location along the testing tube on the behaviour of energy-absorbing, self-drilling rockbolts. The results of this experimental program demonstrated that the location of the split within the host tube controlled both the maximum plate displacement and dissipated energy recorded prior to the rupture of the rockbolt. These additional loading configurations contribute to an improved understanding of the behaviour of Energy-absorbing Self-drilling Rockbolts under impact loading. This has significant practical implications for the selection and design of ground support in block caving operations.
Keywords: hollow core rockbolts